Implementasi Metode Geofence Pada Aplikasi Reminder Berbasis Android - Elfany Rizqi Syaputri; Samsudin Samsudin; Ali Ikhwan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development and utilization of information technology is also used in a way that aims to increase the faith and piety of Muslims in this millennial era. In this digital era, many Muslims are starting to neglect to participate in majlis taklim activities. In this case, the use of the technology used is aimed at increasing the percentage of the majlis taklim congregation which is in the form of a reminder application. This majlis taklim reminder application is an application built using the geofencing method on Android. This application aims to provide reminders in the form of notifications of majlis taklim activities held to users and to make it easier for the majlis taklim committee to disseminate information on the majlis taklim activities that are held. The use of the geofencing method in question is a method used to provide a defined location boundary so as to provide a trigger in the form of a notification to users who are within the boundaries of the area. The notification received by the user is the location of the activity, so it is hoped that this majlis taklim reminder application can increase the percentage of majlis taklim congregations.